A tertiary centre experience comparing new temperature-controlled high-power short-duration ablation technology with standard radiofrequency and cryo-energy ablation. (14th October 2021) - Mavilakandy, A; Sidhu, B; Man, S; Antoun, I; Vali, Z; Almeida, T P; Li, X; Lazdam, M; Ibrahim, M; Chin, S H; Sandilands, A; Somani, R; et al.
Abstract: Introduction: Pulmonary vein isolation (PVI) is an established treatment strategy for atrial fibrillation (AF). Radiofrequency (RF) ablation technology has evolved over the last decade with the very high-power short-duration (vHPSD) temperature-controlled ablation approach emerging as the latest development. The aim of this study was to determine the procedural efficacy, metrics and safety of vHPSD ablation with conventional power-controlled RF (PCRF) ablation and cryo-energy ablation (CRYO). Methods: A prospective single tertiary centre analysis was performed on patients undergoing first time PVI ablation from 2019 to 2020. The population was divided in to 4 treatment arms; vHPSD, high-power short-duration (HPSD), PCRF and CRYO. Demographics, clinical and procedural metrics such as PVI duration, ablation time and sedation requirement were collated. Patients were monitored for perioperative complications. Results: One hundred patients underwent ablation with 25 cases conducted in each arm. Complete PVI was attained in all study subjects. For the vHPSD group, PVI procedural duration, ablation and fluoroscopy times were 71.7±6.35 min, 9.21±0.76 min and 15.1±1.50 min respectively. The HSPD group exhibited total PVI, burn and fluoroscopy times of 90.2±5.59 min (p=0.03), 10.3±2.40 min (p<0.0001) and 34.1±1.67 min (p=0.1) respectively. In comparison, the PCRF group exhibited longer procedure duration, ablation and fluoroscopy times of 93.3±6.50 min (p=0.01), 15.2±1.73 min (p<0.0001), 37.8±2.47 min (p=0.870). Whereas procedural and fluoroscopy times of 96.3±7.1 min (p=0.01) and 18.8±1.31 (p=0.05) were observed in the cryo-ablation group. Procedural doses of morphine and midazolam for the vHPSD, HPSD, PCRF and CRYO group were 11.3 mg + 4.00 mg, 15.5 mg (p=0.0003) + 9.33 mg (p=0.0003), 15.7 mg (p=0.0002) + 8.03 mg (p=0.02), and 8.19 mg (p=0.01) + 4.84 mg (p=0.303) respectively. No adverse procedural events were recorded for the vHPSD while 2 pericardial effusions occurred in the PCRF group, 1 cardiac tamponade in the HPSD group and 2 transient ischaemic attacks in the CRYO group. Conclusion: With the emergence of vHPSD RF ablation, preliminary findings indicate significant potential in reduction of procedural and ablation time. Further analysis is ongoing in order to ascertain longer-term efficacy and patient safety. Funding Acknowledgement: Type of funding sources: None.